Perturbation Analysis for Oblique Projection Generalized Inverses. (25th October 2020) - Du, Fapeng; Nashed, M. Zuhair
Abstract: In this paper, we introduce the notion of stable perturbation of a subspace in Banach space. Utilizing this notion and the gap between subspaces, we develop a perturbation analysis for the oblique projection generalized inverse when the operator T, the range and null space of the projectors have perturbations simultaneously and estimate an upper bound of | | T ¯ P ¯, Q ¯ + − T P, Q + | | . Our results are new and extend the related results on the perturbation analysis of the oblique projection generalized inverse.